2008
DOI: 10.1038/oby.2007.57
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Breastfeeding on Trajectories of Body Fat and BMI throughout Childhood

Abstract: objective:To investigate the effect of breastfeeding in healthy boys and girls on their trajectories of percent body fat (%BF) and BMI standard deviation scores (BMI-SDS) throughout childhood. Methods and Procedures: Analyses of the DOrtmund Nutritional and Anthropometric Longitudinally Designed (DONALD) Study included data from 219 male and 215 female term participants, born between 1984 and 1999, with repeated anthropometric measurements between 0.5 and 7 years and prospective data on duration of breastfeedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 36 publications
0
40
2
2
Order By: Relevance
“…[33,34] The initiation and duration of breastfeeding may influence obesity in later life, although this remains controversial. Some studies have suggested that breastfeeding protects against the development of obesity in children.…”
Section: Discussionmentioning
confidence: 99%
“…[33,34] The initiation and duration of breastfeeding may influence obesity in later life, although this remains controversial. Some studies have suggested that breastfeeding protects against the development of obesity in children.…”
Section: Discussionmentioning
confidence: 99%
“…Variables modeled as fixed effects were breastfeeding status, child age, and potential confounders (birth weight, having elder sibling(s), maternal age, parental educational level, total household income, and parental smoking status at 6 months of age). Child age was used as dummy variables for time as previous study found nonlinearity in the trajectory of BMI (20,21). Then, we evaluated the associations between breastfeeding status and changes in BMI over time, using interaction terms between child age and exclusiveness or duration of breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, childhood adiposity may be influenced by early life events like in utero fetal growth (13), breast feeding (14), and rapidity of weight gain during infancy (13,15). A heavier birth weight has been shown to confer a higher risk of being overweight during childhood and adolescence (16,17).…”
mentioning
confidence: 99%